Synthesis and spectroscopic investigation of a new hexadentate Schiff base ligand with N2O4 donor atoms and related metal complexes - Golbedaghi, Reza; Rezaeivala, Majid; Albeheshti, Leila (European Journal of Chemistry, 2015)
Five new complexes [CdH2L(NO3)]ClO4 (1), [ZnH2L](ClO4)2 (2), [NiH2L](ClO4)2 (3), [CuH2L](ClO4)2 (4) and [CoH2L](ClO4)2 (5) were prepared by reaction of a new Schiff base ligand and different metal ions in 1:1 ratios. The new Schiff base ligand H2L was synthesized by reaction of 2-(4-(2-formylphenoxy)butoxy) benzaldehyde and ethanol amine and characterized with IR, 1H and 13C NMR and elemental analysis. The synthesized complexes were also characterized by IR and elemental analysis in all cases and 1H, 13C NMR and COSY in the case of [CdH2L(NO3)]ClO4 and [ZnH2L](ClO4)2 complexes.